The Effect of Physical Training on Increasing Kick Speed in Taekwondo Athletes - Kurniawan, Ryandhika; Daryanto, Zusyah Porja; Rahmat, Ade (UNIVERSITAS NEGERI MAKASSAR, 2024)
The objective of this study was to investigate the impact of physical training on the improvement of kicking speed in Taekwondo athletes. A pre-test and post-test design was utilized, wherein athletes were asked to perform physical ability tests based on a training menu created for the study. The results of the post-test were compared to the pre-test results to assess the extent to which the athletes' endurance and agility had improved as a result of the treatment. The data analysis methodology employed in this study included calculating the mean of the pre-test and post-test data, calculating the standard deviation of the difference, and performing a paired t-test. The results demonstrated a significant increase in the mean number of kicks from 6.10 to 8.90, indicating that the treatment enhanced the athletes' performance. The higher standard deviation in the post-test (1.91) compared to the pre-test (0.74) suggests that, although athletes' abilities generally improved, there was greater variation among athletes in terms of the extent of their improvement. The results of the paired t-test demonstrated a statistically significant difference between the mean values of the pre-test and post-test, indicating that the treatment significantly enhanced the athletes' kicking speed. The T-count value recorded was -8.51, which was compared to the T-table value generated using a 15% significance threshold and 2.228 degrees of freedom. The conclusion drawn from this study is that a treatment regimen of two weeks or six meetings can improve the ability to perform the dollyo chagi kick-in Taekwondo athletes.